UNDERGRADUATES’ PERCEPTIONS ON THE USE OF FLIPGRID PLATFORM IN SPEAKING CLASSROOM - Aliyu, Muhammad Mukhtar; Jibril, Ahmed Tanimu; Yakubu , Halima Sadiya; Aminu, Ummu-Kaltume (Yavana Bhasha : Journal of English Language Education, 2026)
This study is part of a larger study that investigated the impact of Flipgrid on Nigerian undergraduates' speaking skills and speaking anxiety. Thus, this paper examined the undergraduates’ perceptions regarding the integration of Flipgrid into their speaking classroom. The study employed a questionnaire and semi-structured interviews to gather data from 25 third-year participants. Descriptive statistical analysis was employed to analyse the data. The findings of the analysis revealed positive perceptions of the use Flipgrid platform. Participants explained that the platform can foster engagement, increase confidence, and enhance speaking practice outside the classroom. The findings further showed that the platform increased the participants’ motivation, and collaborative learning skills, and reduced their speaking anxiety. Finally, the study makes some recommendations for practice and further studies. It is, therefore, recommended that Flipgrid be incorporated into speaking classrooms given its potential benefits in enhancing students’ engagement as well as communication skills development. It is also recommended that larger-scale research involving longer treatment durations could be carried out to validate and extend the findings of the present study.